Green Economy in Hotel Business of EU Countries - K. I. Shchetinina (MGIMO University Press, 2013)
Tourism today is one of the fastest growing economic sectors in the world. The article gives a brief review of a new economic paradigm and development model: a green economy. It shows how green investment in European tourism sector can contribute to economically viable and robust growth, decent work creation and poverty alleviation, while improving resource efficiency and minimising environmental degradation. Much of the economic potential for green tourism is found in small and medium-sized enterprises (SMEs), which need better access to financing for investing in green tourism. Investments and policies of European Union government can leverage private sector actions on green tourism.